2018
DOI: 10.33005/ebgc.v1i2.23
|View full text |Cite
|
Sign up to set email alerts
|

Study of Earning Management and Audit Quality in Indonesia

Abstract: The objectivites of the research is to find out empirical evidence of the determine audit quality in mediating the relantionship between KAP size, KAP tenure and earnings managemen. The population of this study was listed companies in the manufacturing sector at the Indonesia Stock Exchange, and the sample was determined based on following criteria: (a) the annual report ended 31 December, (b) not include in financial secto, ect. There were 355 companies meeting the criteria. The technique used is the analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
3
0
1
Order By: Relevance
“…The study by Lu (2017) found that 73.9% of all sampled companies were involved in earning management by inflating their incomes. The quality of audit has been found to have a positive and significant effect on earning management as per the study by Sari and Sari (2019) undertaken in Indonesia.…”
Section: Literature Reviewmentioning
confidence: 84%
“…The study by Lu (2017) found that 73.9% of all sampled companies were involved in earning management by inflating their incomes. The quality of audit has been found to have a positive and significant effect on earning management as per the study by Sari and Sari (2019) undertaken in Indonesia.…”
Section: Literature Reviewmentioning
confidence: 84%
“…Pentingnya kualitas audit ini telah ditekankan oleh beberapa penelitian (Hariady & Haryanto, 2017;Susilawati, 2015;Tjan, 2020), yang menyoroti peranannya dalam mengevaluasi dan mengidentifikasi pelanggaran yang mungkin terjadi. Kualitas audit juga menjadi krusial bagi Kantor Akuntan Publik dalam mempertahankan kepercayaan masyarakat terhadap profesi akuntan public (Djatmiko & Rizkina, 2014;Sari & Hariadi, 2019).…”
Section: Pendahuluanunclassified
“…In the comparison of the two models, the algorithm on the chi-squared test is better or more satisfying if the resulting X 2 value is low; the smaller the X 2 value, the better and more accepted model [20].…”
Section: Goodness Of Fitmentioning
confidence: 99%